2018
DOI: 10.1093/cid/cix1070
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Human Immunodeficiency Virus Type 1 Minority Variants on the Virus Response to a Rilpivirine-Based First-line Regimen

Abstract: Minority resistant variants had no impact on the VR of treatment-naive patients to a rilpivirine-based regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…However, a recent study by Raymond S et al, using the NGS 454 GS-FLX system, showed that drug-resistant minority variants had no impact on the virological failure of treatment-naive patients to a rilpivirine-based regimen [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study by Raymond S et al, using the NGS 454 GS-FLX system, showed that drug-resistant minority variants had no impact on the virological failure of treatment-naive patients to a rilpivirine-based regimen [23].…”
Section: Introductionmentioning
confidence: 99%
“…Ultradeep sequencing technologies capable of detecting variants present at a frequency as low as 1% of the virus population, for example, next-generation sequencing (NGS), are slowly being introduced into clinical microbiology diagnostic laboratories. However, the evidence for the clinical significance of drug-resistant minority variants (DRMinVs) is contradictory, and more data are required to inform their interpretation in clinical management of HIV-infected individuals using validated assays and large-scale clinical studies [2][3][4][5][6][7][8][9][10].…”
mentioning
confidence: 99%
“…Second, the analyzed data was generated by research laboratories that adopted measures to improve the detection of low frequency variants, avoided samples with very low virus loads, and made their data publicly available. Indeed, previous studies have suggested that a five percent threshold is likely to be more reproducible in clinical settings [7,24,32,33].…”
Section: Discussionmentioning
confidence: 99%